2016
DOI: 10.5114/jcb.2016.59216
|View full text |Cite
|
Sign up to set email alerts
|

Single-fraction high-dose-rate brachytherapy using real-time transrectal ultrasound based planning in combination with external beam radiotherapy for prostate cancer: dosimetrics and early clinical results

Abstract: PurposeTo validate the feasibility of a single-fraction high-dose-rate brachytherapy (HDRBT) boost for prostate cancer using real-time transrectal ultrasound (TRUS) based planning.Material and methodsFrom August 2012 to September 2015, 126 patients underwent a single-fraction HDRBT boost of 15 Gy using real-time TRUS based planning. External beam radiation therapy (EBRT) (37.5 Gy/15 fractions, 44 Gy/22 fractions, or 45 Gy/25 fractions) was performed before (31%) or after (69%) HDRBT boost. Genito-urinary (GU) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…This evolution has substantially improved workflow efficiencies (41), and was enabled by the technical development of 3D TRUS through new robotic aids and computational tools. Although depiction of prostate boundaries with TRUS is superior to that on CT, uncertainties remain at the anterior gland because of echogenic artifacts created by implanted catheters.…”
Section: Resultsmentioning
confidence: 99%
“…This evolution has substantially improved workflow efficiencies (41), and was enabled by the technical development of 3D TRUS through new robotic aids and computational tools. Although depiction of prostate boundaries with TRUS is superior to that on CT, uncertainties remain at the anterior gland because of echogenic artifacts created by implanted catheters.…”
Section: Resultsmentioning
confidence: 99%
“…In cases of uncertain diagnosis repeat biopsies are required, adding significant delay before diagnosis can be obtained and a treatment chosen, and increasing risk for the patient. The new technique also shows great potential in interventional medicine applications beyond biopsies to optimize targeted treatment methods such as in laser-induced thermotherapy (LIIT) 46 , brachytherapy 47 , 48 or therapeutics injection of viruses into tumors.…”
Section: Discussionmentioning
confidence: 99%
“…While retrospective data report that the benefit of a HDR boost on cancer-specific mortality in intermediate and high-risk prostate cancer patients remains unclear [ 5 ], other reports show that a HDR boost following EBRT increases survival rates with few treatment-related toxicities [ 6 , 7 , 8 ]. Lauche et al [ 9 ] reported that the addition of a single-fraction HDR boost (15 Gy) to EBRT using real-time transrectal ultrasound (TRUS) planning provided high dosimetry quality with no patients experiencing ≥ 2 GI toxicity (follow-up 10 months). While previous reports also suggest that patients receiving EBRT plus HDR brachytherapy experience lower rates of incontinence and sexual dysfunction than patients receiving prostatectomy, they may experience chronic radiation proctitis with rectal wall bleeding up to two years after treatment [ 10 , 11 ].…”
Section: Purposementioning
confidence: 99%